Organic System Talcott Parsons VS Utilitarianism Perspective in The Social Life System of Street Children - Samiha, Yulia Tri; Riswanda, Jhon; Jaya, Andi Candra; Boty, Middya; Romadhan, Muhammad Fauzi; Wijaya, Agung (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
The phenomenon of street children in big cities, including Palembang City, is a complex social problem that requires special attention. These children generally come from poor or unstable families and are forced to work on the streets to survive or avoid dysfunctional home conditions. This study aims to analyze the social life system of street children through the perspective of Talcott Parsons' organic system and the perspective of utilitarianism. The method used is qualitative analysis based on interviews, street children's questionnaires, and Palembang City community questionnaires. Based on the organic system theory, street children are the result of family failure in providing social support and stability, thus encouraging children to meet their needs independently. Meanwhile, from the perspective of utilitarianism, although living on the streets is full of risks, these children can still feel happiness through freedom, autonomy, and the opportunity to earn their living. Thus, street children's existence is influenced by family failure and rational decisions that give them a sense of comfort and freedom outside the home, and economic factors strongly influence both.